Speech by Prof. Paul Musili Wambua, Chancellor, University of Embu during the 3rd graduation Ceremony - Wambua, Paul M. (University of Embu, 2018)
Speech by Prof. Paul Musili Wambua, Chancellor, University of Embu during the 3rd graduation Ceremony at University of Embu on 14thseptember 2018 At 9.00 A.M.